DISFEMISME TUTURAN PEDAGANG PASAR BANGKINANG - Jannah, Wirdatul; Auzar, Auzar; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrac: The purpose of this research was to discuss the speech dysfemism ofBangkinang market traditional traders. This research purposed to describe the formand meaning of dysfemism spoken by Bangkinang market traders. In this research, theresearch data source is the Bangkinang market trader. The research data was obtainedfrom recordings and field notes of merchant conversations containing disfemism. Thedata collection technique of research on Bangkinang market traders' speech dysfemismis observation, field notes, and recordings by looking for words and sentences thatcontain disfemism. this method is operationalized by collecting data that is relevant tothe writing problem. The analysis technique used in analyzing data in words andsentences containing disfemism is descriptive analysis techniques. Descriptive analysistechniques are used to describe the form and meaning of speech dysfemism Bangkinangmarket traders. The data of this research amounted to 30 data consisting of 20 wordform data, 5 data form phrases, and 5 forms of expressions.Key Words: Dysfemism, speech , Bangkinang.